Las variedades del español de Perú: un estudio desde la dialectología - Fallas Monge, Johnny (2013)
This article describes all levels of the Spanish from Perú: phonetic - phological, morphosyntactic, lexicon and sociolinguistic. This study is based on previous investigations, dialectology mainly, it also includes social - historical data, and the contact of indigenous lingual such as quechua and aimara with Spanish that contribut to the way Peruvians speak. The bibliographical and descriptive studies, similar to this, have the purpose of revitalizing the indigenous languages, due to the risk of extinction. With this description we pretend to safeguard the linguistic and cultural patrimony of America.